Pharyngeal shape and dimensions in healthy subjects, snorers, and patients with obstructive sleep apnoea. Issue 10 (October 1990) - Rodenstein, D O; Dooms, G; Thomas, Y; Liistro, G; Stanescu, D C; Culée, C; Aubert-Tulkens, G
Abstract : To characterise the relation between pharyngeal anatomy and sleep related disordered breathing, 17 men with complaints of snoring were studied by all night polysomnography. Ten of them had obstructive sleep apnoea (mean (SD) apnoea-hypopnoea index 56.3 (41.7), age 52 (10) years, body mass index 31.4 (5.3) kg/m2); whereas seven were simple snorers (apnoea-hypopnoea index 6.7 (4.6), age 40 (17) years, body mass index 25.9 (4.3) kg/m2). The pharynx was studied by magnetic resonance imaging in all patients and in a group of eight healthy subjects (age 27 (6) years, body mass index 21.8 (2.2) kg/m2, both significantly lower than in the patients; p less than 0.05). On the midsagittal section and six transverse sections equally spaced between the nasopharynx and the hypopharynx several anatomical measurements were performed. Results showed that there was no difference between groups in most magnetic resonance imaging measurements, but that on transverse sections the pharyngeal cross section had an elliptic shape with the long axis oriented in the coronal plane in normal subjects, whereas in apnoeic and snoring patients the pharynx was circular or had an elliptic shape but with the long axis oriented in the sagittal plane. It is suggested that the change in pharyngeal cross sectional shape, secondary to a reduction in pharyngeal transverse diameter, may be related to the risk of developing sleep related disordered breathing.